2009
DOI: 10.1080/09670260902855873
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular characteristics of selected species ofMinidiscus(Bacillariophyta, Thalassiosiraceae)

Abstract: We report on taxonomically distinguishing morphological features of six diatom taxa from the marine, nanoplanktonic genus, Minidiscus, found in Eastern Canada and neighbouring waters. Four of the six were also investigated using genetic approaches. We found that the culture deposited in the Provasoli-Guillard National Center for Culture of Marine Phytoplankton (CCMP) as CCMP 496 was morphologically closest to the published type image of M. trioculatus, whereas other isolates were morphologically and/or genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 38 publications
2
35
0
2
Order By: Relevance
“…One was the exterior fluted tube-structures of the fultoportulae. Kaczmarska et al 2009 showed that these structures produce chitin filaments. Similar chitin filaments are found in other small Thalassiosira (Martin-Cereceda and Cox 2011) and Cyclotella , and they have been linked to reducing sinking rate (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…One was the exterior fluted tube-structures of the fultoportulae. Kaczmarska et al 2009 showed that these structures produce chitin filaments. Similar chitin filaments are found in other small Thalassiosira (Martin-Cereceda and Cox 2011) and Cyclotella , and they have been linked to reducing sinking rate (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative possibility is that the chitin filaments could interfere with grazing by flagellates and ciliates, because M. comicus lives in a nanno-habitat along with other small species, such as Parmales. Other possible functions might come from an observation by Kaczmarska et al (2009) that cells of a close relative, Minidiscus chilensis, which were collected from surface sediments, had projecting chitin filaments. It is possible that the filaments, which can be over 30 μm long, could help in the resuspension of cells back into the water column by bridging across the boundary layer at the sediment surface.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations